1996
DOI: 10.1021/jm950907l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Activity of a Novel Series of 3-Biarylquinuclidine Squalene Synthase Inhibitors

Abstract: Quinuclidines with a 3-biaryl substituent are a new class of potent, orally active squalene synthase (SQS) inhibitors. Variants around these rigid structures indicate key structural requirements for cationic SQS inhibitors. Thus the lower in vitro potency found for quinuclidines bearing 3-substituents, which did not overlay the biphenyl group of 3-(biphenyl-4-yl)-3-hydroxyquinuclidine (2) (IC50 = 16 nM, rat microsomal SQS), implied a directional requirement for the 3-substituent. Similarly, the lower potency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 21 publications
2
34
1
Order By: Relevance
“…Instead, complicated mixtures were formed. In contrast to these results we found that similar treatment of the corresponding N-methyldiethanolamine boronates protected esters 1 resulted in clean bromine-lithium exchange, 13 and subsequent quench with sulfur dioxide resulted in immediate precipitation of the lithium sulfinates (2a,b) which could be isolated in yields of 94% and 99%, respectively (Scheme 1). Possibly the nitrogen atom in the N-methyldiethanolamine protection group brings the boron atom in a tetrahedral and more protected state via B-N interaction, thereby making it less susceptible for attack of the butyl lithium.…”
contrasting
confidence: 65%
“…Instead, complicated mixtures were formed. In contrast to these results we found that similar treatment of the corresponding N-methyldiethanolamine boronates protected esters 1 resulted in clean bromine-lithium exchange, 13 and subsequent quench with sulfur dioxide resulted in immediate precipitation of the lithium sulfinates (2a,b) which could be isolated in yields of 94% and 99%, respectively (Scheme 1). Possibly the nitrogen atom in the N-methyldiethanolamine protection group brings the boron atom in a tetrahedral and more protected state via B-N interaction, thereby making it less susceptible for attack of the butyl lithium.…”
contrasting
confidence: 65%
“…Nonetheless structural optimization led to the identification of compounds with good biopharmaceutical properties, including reasonable oral bioavailability (Ishihara et al, 2004). Quinuclidine derivatives in particular, such as 33 and 34 (Brown et al, 1996), exhibited an equal or better pharmacological profile to statins in lowering cholesterol levels in hamsters, guinea pigs and Rhesus monkeys (Amin et al, 1997; Brown et al, 1997). However, none of these compounds were advanced to clinical trials; it is noteworthy that the quinuclidine structural motif is believed to be responsible for the toxicities associated with antimalarial drugs, such as quinine.…”
Section: Isoprenoids Fpps/ggpps and Neurodegeneration—the Current Hypmentioning
confidence: 99%
“…A similar rationale has been advanced to explain the potent anti-SQS activity of arylquinuclidine derivatives against both mammalian and T.cruzi SQS [28,29]. Based on this hypothesis, it should be possible to design new and more potent SQS inhibitors, using WC-9 as lead drug.…”
Section: Introductionmentioning
confidence: 99%